Novel CH4-fueled dual expansion oxy-combustion cycle for power and cooling production: Thermodynamic and economic analysis and optimization - Hadelu, Leila Mohammadi; Noorpoor, Arshiya; Boyaghchi, Fateme Ahmadi (Energy (Oxford), 2025)
The present work performs the thermodynamic and economic analysis of the CH4-fueled dual expansion oxy-combustion power cycle (DEOPC) to demonstrate how the near-critical condition of separated CO2 has the potential of cooling production in an innovative configuration equipped by ejector refrigeration section (DEOPEC). The proposed system features power and cooling production advantages with relatively 100 % CO2 capturing. A parametric assessment is carried out to investigate both systems' thermodynamic and economic criteria by varying the substantial design input. Furthermore, the products and their costs are optimized using the multi-objective artificial hummingbird algorithm and decision-making procedure. According to the outcomes, at optimum conditions, DEOPEC, with a 22.06 % reduction in power output due to the increase of compression work, produces a 940.052 kW cooling load, and its energy efficiency can reach 87.77 %, indicating 2.35 times that of DEOPC. Although the cost rate in DEOPEC increases by 70.94 $/h, its investment cost is lower than that of DEOPEC. The economic results indicate the superiority of DEOPEC due to the high net present value (NPV) of 17.73 M$ and low payback period (PP) of 4.08 years. Moreover, the levelized cost of energy (LCOE) may reduce by 0.028 $/kWh, which is 21.8 % lower than that of DEOPC. •A dual expansion oxy-combustion power cycle (DEOPC) is introduced.•A near-critical condition of CO2 is considered as the refrigerant.•DEOPC is redesigned and equipped with an ejector refrigeration section (DEOPEC).•DEOPEC's energy efficiency reaches 2.35 times that of DEOPC.•The levelized cost of energy can reduce by 0.028 $/kWh in DEOPEC.